68Ga-DOTATATE and 123I-mIBG as imaging biomarkers of disease localisation in metastatic neuroblastoma: implications for molecular radiotherapy. Issue 11 (November 2020) - Gains, Jennifer E.; Aldridge, Matthew D.; Mattoli, Maria Vittoria; Bomanji, Jamshed B.; Biassoni, Lorenzo; Shankar, Ananth; Gaze, Mark N.
Abstract : Purpose: Iodine-131-labelled meta-iodobenzylguanidine ( 131 I-mIBG) and lutetium-177-labelled DOTATATE ( 177 Lu-DOTATATE) are used for molecular radiotherapy of metastatic neuroblastoma. These are taken up by the noradrenaline transporter (NAT) and the somatostatin receptor subtype 2 (SSTR-2), respectively. Scintigraphy of iodine-123-labelled meta-iodobenzylguanidine ( 123 I-mIBG) and gallium-68 DOTATATE ( 68 Ga-DOTATATE) PET are used to select patients for therapy. These demonstrate the extent and location of tumour, and avidity of uptake by cells expressing NAT and SSTR-2, respectively. This study compared the similarities and differences in the anatomical distribution of these two imaging biomarkers in an unselected series of patients with metastatic neuroblastoma undergoing assessment for molecular radiotherapy. Methods: Paired whole-body planar 123 I-mIBG views and 68 Ga-DOTATATE maximum intensity projection PET scans of metastatic neuroblastoma patients were visually compared. The disease extent was assessed by a semiquantitative scoring method. Results: Paired scans from 42 patients were reviewed. 68 Ga-DOTATATE scans were positive in all patients, 123 I-mIBG scans were negative in two. In two patients, there was a mismatch, with some lesions identified only on the 123 I-mIBG scan, and others visible only on the 68 Ga-DOTATATE scan. Conclusion: 68 Ga-DOTATATE and 123 I-mIBG scans yield complementary information. For a more comprehensive assessment, consideration could be given to the use of both 123 I-mIBG and 68 Ga-DOTATATE imaging scans. Because of the heterogeneity of distribution of molecular targets revealed by these techniques, a combination of both 131 I-mIBG and 177 Lu-DOTATATE molecular radiotherapy may possibly be more effective than either alone.